Glaucoma; Vol.7 - Paul L Kaufman (Mosby-Wolfe, 1991)
The book deals with a disease family that necessitates integrating all of these approaches. It encompasses and integrates the basic biology and pathobiology of the tissues and physiologic processes with the clinical manifestations, dignostic technologies, and therapeutic modalities relevant to this disease family